Economic and legal aspects of personal bankruptcy - Edyta Iwona Piątek (Economic and Environmental Studies (E&ES), 2019)
When a new act on bankruptcy law entered into force on 1 January 2016, it introduced changes in the scope of personal bankruptcy. The article points to the economic aspects of legal solutions provided for in the new regulation for indebted natural persons, significant on a micro and macro scale. At the same time, it points to the problems in the personal bankruptcy procedure which had existed before the amended Act entered into force, and the problems encountered by debtors and courts in connection with these amendments. The article is based on the author's experience in preparing applications for filling for personal bankruptcy and interviews with the judges employed in the bankruptcy and restructuring section of District Courts. The results of conducted observations and interviews were compared to practical cases which are the subject of bankruptcy applications studied as part of the research project
Keywords: K35; G33; 330; restructuring; bankruptcy; consumer; restructuring; bankruptcy; consumer